2018
DOI: 10.1002/ps.4936
|View full text |Cite
|
Sign up to set email alerts
|

Comparative CYP‐omic analysis between the DDT‐susceptible and ‐resistant Drosophila melanogaster strains 91‐C and 91‐R

Abstract: Our results demonstrate that a combination of changes in P450 protein-coding regions and transcript levels are possibly associated with DDT resistance, and thereby suggest that selection for variant function may occur within this gene family in response to chronic DDT exposure. © 2018 Society of Chemical Industry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 90 publications
2
12
0
Order By: Relevance
“…The present study demonstrated that members for the miR-310s cluster interact with target binding sites within 3ʹ-UTR sequences of cytochrome P450, thereby regulating transcript levels in vivo. Specifically, we showed here that transcript from two cytochrome P450 genes, Cyp6g1 and Cyp6g2, are up-regulated in the DDT-resistant strain 91-R as compared to the -susceptible strains 91-C and Canton-S, reconfirming our previously published results 12,31 . Previous studies provide supporting evidence that high to moderate level DDT resistance is polygenic in Drosophila, with multiple resistance genes, including P450s, associated with the DDT resistance phenotype [8][9][10] .…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The present study demonstrated that members for the miR-310s cluster interact with target binding sites within 3ʹ-UTR sequences of cytochrome P450, thereby regulating transcript levels in vivo. Specifically, we showed here that transcript from two cytochrome P450 genes, Cyp6g1 and Cyp6g2, are up-regulated in the DDT-resistant strain 91-R as compared to the -susceptible strains 91-C and Canton-S, reconfirming our previously published results 12,31 . Previous studies provide supporting evidence that high to moderate level DDT resistance is polygenic in Drosophila, with multiple resistance genes, including P450s, associated with the DDT resistance phenotype [8][9][10] .…”
Section: Discussionsupporting
confidence: 91%
“…The Cyp6 subfamily has been associated with DDT resistance and cross-resistance to neonicotinoid insecticides 32,33 . For example, statistically significant differences in expression were documented for Cyp6a2, Cyp6a8, Cyp6g1, Cyp6g2, and Cyp6w1 in DDT-resistant 91-R and Wisconsin strains as compared to DDT-susceptible Canton-S and 91-C strains; relatedly, previous evidence of significant changes in expression of Cyp6 subfamily is functionally involved in DDT resistance in Drosophila 12,19,34 . Moreover, overexpression of the CYP6W1-Ala370 allele in transgenic Drosophila was sufficient to confer low levels of DDT tolerance relative to CYP6W1-Val370 and CYP6W1-Gly370 16 .…”
Section: Discussionmentioning
confidence: 77%
“…The differentially expressed Cyp12d1-p is positioned within the Rst(2)DDT locus, and Cyp12d1-p and Cyp12a4 were upregulated in 91-R compared with 91-C within previous studies ( Pedra et al 2004 , Festucci-Buselli et al 2005 , Seong et al 2018 ), suggesting P450s may be involved in genetic responses to DDT. Specifically, DDT exposure was shown to induce Cyp12d1 in the DDT-resistant field-selected fly strains Wisconsin and Hikone-R, as well as the laboratory-selected 91-R strain ( Festucci-Buselli et al 2005 ).…”
Section: Discussionmentioning
confidence: 49%
“…Moreover, upregulation of Cyp12a4 was previously documented in Drosophila as a mechanism of resistance to lufenuron, an insect growth regulator that disrupts chitin synthesis and is typically used as a control method for the cat flea, Ctenocephalides felis Bouché 1835 (Siphonaptera: Pulicidae) ( Bogwitz et al 2005 ). Interestingly, a mutation in the Cyp12d1-p gene of 91-R was predicted to produce a nonfunctional protein, which was not present in 91-C ( McDonnell et al 2012 , Seong et al 2018 ) that could potentially aid in lowering ROS accumulation in the mitochondria. Alternatively, because some P450s are implicated in cuticle formation, possibly through their regulation of ecdysone levels ( Sztal et al 2012 ), this mutation could modify cuticular hydrocarbon composition that results in decreased insecticide absorption ( Balabanidou et al 2016 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation